Assessment of the optical and electrical properties of light-emitting diodes containing carbon-based nanostructures and plasmonic nanoparticles: a review - Nagpal, Keshav; Rauwel, Erwan; Ducroquet, Frédérique; Rauwel, Protima (Beilstein Journal of Nanotechnology, 2021)
Light-emitting diodes (LED) are widely employed in display applications and lighting systems. Further research on LED that incorporates carbon nanostructures and metal nanoparticles exhibiting surface plasmon resonance has demonstrated a significant improvement in device performance. These devices offer lower turn-on voltages, higher external quantum efficiencies, and luminance. De facto, plasmonic nanoparticles, such as Au and Ag have boosted the luminance of red, green, and blue emissions. When combined with carbon nanostructures they additionally offer new possibilities towards lightweight and flexible devices with better thermal management. This review surveys the diverse possibilities to combine various inorganic, organic, and carbon nanostructures along with plasmonic nanoparticles. Such combinations would allow an enhancement in the overall properties of LED.
Keywords: carbon nanotubes (CNT); graphene; light-emitting diodes (LED); plasmonic nanoparticles; quantum dots